P217 High demand for an MSM clinic pilot in a district general hospital. (18th May 2015) - Oduru, Mamatha; Wainwright, Emma; Burnett, Janice; Tang, Alan
Abstract : Background/introduction: A tailored sexual health service for men who have sex with men (MSM) was piloted in a district general hospital. This was in response to a 'Gay Pride' survey in which 80% of surveyed attendees requested a specialised local service. Aim(s)/objectives: This clinic explored the feasibility and acceptability of a targeted MSM service in the district general hospital setting. Methods: The pilot had 9 clinics over 3 months. Each patient was fast-tracked to a multidisciplinary team (doctor, nurse and health advisor). A rapid HIV test (result within 24 h) was offered to every patient as point of care testing was unavailable in the service. Data and patient feedback were analysed in SPSS version 22. Results: A total of 13 patients attended the clinic (new, N = 12, follow up, N = 1). Age range was 22 to 67 years old (mean 33.7, standard deviation 13.27) and all were Caucasian. 6/13 attended for an asymptomatic screen; the prevalence of sexually transmitted infections (STI's) was 46%. All tested HIV negative. 61.5% had no prior immunity to Hepatitis B. 92.3% considered the rapid HIV test an incentive to attend and 100% wanted a future point of care test. There was favourable patient feedback. Discussion/conclusion: The clinic pilot was positively received and the majority rated it preferable to the routine genitourinary clinic. There was a high prevalence of STI's and high rate of opportunistic Hepatitis B vaccination. There is a notable demand for rapid HIV testing. Our tailored MSM clinic encouraged attendance in a high risk provincial population.